PENINGKATAN FOKUS BELAJAR MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN ANIMASI 3D DI KELAS II SDN PISANGCANDI 1 MALANG - Dwi Cahyati, Linda; Yudiono, Udik; Farida, Nun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to improve students' focus on mathematics learning through the use of the Numbered Heads Together (NHT) cooperative learning model combined with three-dimensional (3D) animation media for second-grade students at Pisangcandi 1 Elementary School, Malang. The underlying problem was students' low concentration during mathematics learning, as evidenced by a lack of attention, low active engagement, and a suboptimal understanding of mathematical concepts. The research method used was Classroom Action Research (CAR) using the Kemmis and McTaggart model, implemented in two cycles. Twenty-five second-grade students at Pisangcandi 1 Elementary School, Malang, participated in the study. Data collection included observation, pre- and post-test learning focus tests, and documentation of learning activities. The results showed that the implementation of the Numbered Heads Together (NHT) model with 3D animation was able to gradually improve students' focus on mathematics learning. The average pretest score of 36 (SD = 21.25) increased to 61 (SD = 27.47) in the posttest, with an N-Gain score of 0.425, which is in the moderate category. Thus, the use of the NHT model combined with 3D animation media is considered effective in helping improve the focus of elementary school students' mathematics learning.